Microfluidic salt precipitation: implications for geological CO2 storage. Issue 20 (14th September 2020) - Ho, Tsai-Hsing Martin; Tsai, Peichun Amy
Abstract : Novel microfluidic visualizations reveal the simultaneous dynamics of salt nucleation and fluid drying rates while mimicking carbon capture and storage processes. Abstract : Salt precipitation in porous media can detrimentally hinder the processes of carbon capture and storage (CCS) in deep saline aquifers because pore-blocking salt crystals can decrease the injectivity of wells and formation permeabilities. It is, however, challenging to unravel the pore-scale dynamics and underlying mechanisms of salt nucleation using conventional core-flooding techniques. Here, we conduct microfluidic experiments to reveal the high-resolution, pore-scale measurements of the de-wetting patterns and drying rate of brine and subsequent salt precipitation during gas injection. We investigate the effects of pore structures and brine concentrations. The results show three distinct stages: (I) initial, (II) rapid growth, and (III) final phases in the progression of salt nucleation, with different rates and size distributions upon brine drying. Two types of crystal patterns, bulk crystal and polycrystalline aggregate, are observed. In addition, most of the large salt deposits (≥0.5 × 10 5 μm 2 ) are precipitated at the near outlet region during the second rapid growth stage. The influence of porosity is demonstrated by correlating the brine-drying and salt-precipitation speeds during the second rapid growth phase.